An Exploration Of Clinical Governance Implementation And Assessment Challenges In Qazvin Teaching Hospitals: A Qualitative Study - Saeed Asefzadeh; Sanaz Taghizadeh; Ali Heyrani; Rafat Mohebbifar; Jalal Arabloo (Tehran University of Medical Sciences, 2015)
Background and Aim: To improve the implementation of clinical governance (CG) in Iranchr('39')s hospitals, awareness of various aspects of its implementation and assessment is important. The aim of this study was to find out the obstacles and challenges of clinical governance implementation and assessment in Qazvin teaching hospitals. Materials and Methods: Semi-structured interviews with 17 senior managers, clinical staff and clinical governance experts were conducted in six hospitals of Qazvin University of Medical Sciences (QUMS). To analyze the collected data, framework analysis was used. Results: The challenges and obstacles of CG implementation in Qazvin teaching hospitals were explained using three themes of (1) challenges of CG implementation, (2) improvement in seven dimensions of CG, and (3) challenges of CG implementation assessment. Conclusion: The results of this study show that CG implementation needs to address three issues: improving clinical staff awareness about CG, changing organizational culture so as to make it more receptive to CG, and creating higher levels of cooperation among physicians, managers, patients, specialists, and professionals. The supportive role of top management in addressing the three issues and in providing resources and other infrastructures is obviously essent